Revitalisasi Pembelajaran Musik melalui Pengembangan Kemampuan Dasar musikal Peserta Didik di Taman Kanak-Kanak - Indra Yeni (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2012)
Music learning in kindergarten so far focused on the development of singing through habituation, so the results are not optimal. This study aims to describe the music learning to develop basic musical skills of students in kindergarten. This study used a qualitative approach, which is implemented in kindergarten Dharmawanita UNP. Data collected by observation, interviews, and documentation, and then analyzed according to the method developed by Miles and Huberman. The results showed that the learning of music in the classroom as an activity carried out by the main dedicated music teacher and allocating specific time for music learning on a regular basis to optimize the development of basic musical skills of learners. Keywords: learning, music, menyanyi, musical ability